The Effect of Slow Deep Breathing on Lowering Blood Pressure in Elderly People with Hypertension in Karangdowo Village, Sumberrejo District, Bojonegoro Regency - Siti Khusnul Khotimah; Arifal Aris; Abdul Majid; Nur Laili Rahmawati; Hanny Mareta Putri; M. Romadhon Ilham B; Rizqi Indah Fitrianti (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Hypertension or high blood pressure is a condition in which a person experiences an increase in blood pressure above normal for a long time. The purpose of this study was to determine the effect before and after administration of Slow Deep Breathing on reducing blood pressure in patients with hypertension. This research method used a one group pre-posttest design with a purposive sampling technique of 33 respondents. The research data were taken using a sphygmomanometer blood pressure observation sheet and then analyzed using the Wilcoxon signed rank test. The results showed that the blood pressure of elderly people with hypertension before Slow Deep Breathing therapy obtained an average of 2.33, while after S DB therapy, the average blood pressure decreased to 1.52. The results of the Wilcoxon signed rank test was with a significant value of p = 0.000 (p <0.05). In other words, H1 was accepted and H0 was rejected, meaning that there was an effect before and after SDB on blood pressure in elderly people with hypertension. In conclusion, Slow Deep Breathing therapy with breathing techniques slowly and deeply uses the diaphragm muscles, which allows the abdomen to be lifted slowly and the chest to expand fully. Thus, there is an effect on lowering blood pressure.